Microbial Community Structure and Chemical Constituents in Shinkiku, a Fermented Crude Drug Used in Kampo Medicine - Wang, Zitai; Okutsu, Kayu; Futagami, Taiki; Yoshizaki, Yumiko; Tamaki, Hisanori; Maruyama, Takuro; Toume, Kazufumi; Komatsu, Katsuko; Hashimoto, Fumio; Takamine, Kazunori (Frontiers in Nutrition, 2020)
Shinkiku (Massa Medicata Fermentata) is a traditional crude drug used to treat anorexia and dyspepsia of elder patients in east Asia. Shinkiku is generally prepared by the microbial fermentation of wheat and herbs. Shinkiku is also used in Japanese Kampo medicine as a component of 半夏白朮天麻湯 (Hangebyakujutsutemmato). However, the quality of shinkiku varies by manufacture because there are no reference standards to control the quality of medicinal shinkiku. Thus, we aim to characterize the quality of various commercially available shinkiku by chemical and microbial analysis. We collected 13 shinkiku products manufactured in China and Korea and investigated the microbial structure and chemical constituents. Amplicon sequence analysis revealed that Aspergillus sp. was common microorganism in shinkiku products. Digestive enzymes (alpha-amylase, protease, and lipase), organic acids (ferulic acid, citric acid, lactic acid, and acetic acid), and 39 volatile compounds were commonly found in shinkiku products. Although there were some commonalities in shinkiku products, microbial and chemical characteristic considerably differed as per the manufacturer. Aspergillus sp. was predominant in Korean products, and Korean products showed higher enzyme activities than Chinese products. Meanwhile, Bacillus sp. was commonly detected in Chinese shinkiku, and ferulic acid was higher in Chinese products. Principal component analysis based on the GC-MS peak area of the volatiles also clearly distinguished shinkiku products manufactured in China from those in Korea. Chinese products contained higher amounts of benzaldehyde and anethole than Korean ones. Korean products were further separated into two groups: one with relatively higher linalool and terpinen-4-ol and another with higher hexanoic acid and 1-octen-3-ol. Thus, our study revealed the commonality and diversity of commercial shinkiku products, in which the commonalities can possibly be the reference standard for quality control of shinkiku, and the diversity suggested the importance of microbial management to stabilize the quality of shinkiku.